Prof dr L J S Steenkamp: "n Oorsig van sy lewe en werk - Merwe, P. J. van der (Hervormde teologiese studies, 1999)
Prof Dr L J S Steenkamp: A review of his life and career. Prof Lourens Johannes Stephanus Steenkamp retired on medical grounds from his teaching post at the Faculty of Theology (Section A), University of Pretoria, on 31 March 1999. This article contains some biographical notes and a brief review of his career. Lourens Steenkamp's career in the ministry of the Nederduitsch Hervormde Kerk (NHK) started in 1973 in a small town on the Mpumalanga platteland. In 1987 he received the DPhil degree of the University of Pretoia. The title of his thesis was "Aristotle's concept of God". His career took a new turn in 1989 when he was appointed director of the NHK's Institute for the Training of Office Bearers and Church Members and head of the Centre for Theological Research and Instruction (STNT) of the Faculty of Theology (Section A), University of Pretoria. In 1994 he moved over to the Faculty as full-time organiser of the centrefs programmes and pat-time lecturer in Philosophy of Religion. His main interests were two-fold: theology and educaional policy matters. His contribution in both of these fields is discussed and reviewed.